Accurate numerical simulation of the far-field tsunami caused by the 2011 Tohoku earthquake, including the effects of Boussinesq dispersion, seawater density stratification, elastic loading, and gravitational potential change. (March 2017) - Baba, Toshitaka; Allgeyer, Sebastien; Hossen, Jakir; Cummins, Phil R.; Tsushima, Hiroaki; Imai, Kentaro; Yamashita, Kei; Kato, Toshihiro
Highlights: Accurate far-field tsunami simulation with a finite difference scheme. Consideration of Boussinesq dispersion and water density stratification. Consideration of elastic loading and gravitational potential change. Tsunami computation using a high-performance computer. Abstract: In this study, we considered the accurate calculation of far-field tsunami waveforms by using the shallow water equations and accounting for the effects of Boussinesq dispersion, seawater density stratification, elastic loading, and gravitational potential change in a finite difference scheme. By comparing numerical simulations that included and excluded each of these effects with the observed waveforms of the 2011 Tohoku tsunami, we found that all of these effects are significant and resolvable in the far field by the current generation of deep ocean-bottom pressure gauges. Our calculations using previously published, high-resolution models of the 2011 Tohoku tsunami source exhibited excellent agreement with the observed waveforms to a degree that has previously been possible only with near-field or regional observations. We suggest that the ability to model far-field tsunamis with high accuracy has important implications for tsunami source and hazard studies.